1996
DOI: 10.1111/j.1467-9507.1996.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Family Guidance in Low‐Income Mexican‐American and European‐American Families*

Abstract: This two‐part study applied an ecocultural perspective to socialization of daily and long‐term goals in low‐income Mexican‐American and European‐American families with children in third, fifth, and seventh grades. The first part of the study examined family members' participation and parents' socialization goals and guidance strategies for their children's daily household chores and homework activities. The second part of the study examined parents' long‐term aspirations and guidance strategies for their child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 15 publications
1
46
0
Order By: Relevance
“…Due to barriers that low-income immigrants face in connecting to individuals of higher social classes, immigrant parents' social ties to U.S.-born friends likely do not provide immigrant parents with access to social resources (i.e., social capital) that might be possible for more socioeconomically advantaged populations (Stanton-Salazar and Dornbush 1995). Rather, for Mexican immigrant families, social ties with Mexican-origin families may be valuable by providing adolescents with a stronger sense of cultural identity and, in turn, social support that can benefit youth's academic success (Azmitia et al 1996(Azmitia et al , 2009. A second facet of cultural orientation associated with less educational attainment is the value that youth place on early paid work.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Due to barriers that low-income immigrants face in connecting to individuals of higher social classes, immigrant parents' social ties to U.S.-born friends likely do not provide immigrant parents with access to social resources (i.e., social capital) that might be possible for more socioeconomically advantaged populations (Stanton-Salazar and Dornbush 1995). Rather, for Mexican immigrant families, social ties with Mexican-origin families may be valuable by providing adolescents with a stronger sense of cultural identity and, in turn, social support that can benefit youth's academic success (Azmitia et al 1996(Azmitia et al , 2009. A second facet of cultural orientation associated with less educational attainment is the value that youth place on early paid work.…”
Section: Discussionmentioning
confidence: 93%
“…Feeling connected to one's cultural group through shared social ties promotes youth's healthy development (Duke et al 2009) and can reinforce culture-specific beliefs and values for immigrant youth. In the same way, same-ethnic friends among parents can provide social support to families that supports youth's success in school (Azmitia et al 1996(Azmitia et al , 2009). …”
Section: Cultural Orientationsmentioning
confidence: 94%
“…In contrast, some ethnographic work with immigrant and second-generation Mexican-American families has found that children were expected to participate and contribute to household responsibilities and everyday tasks at early ages (see studies by Azmitia et al 1996;Delgado-Gaitan 1993). As noted by Harwood et al (2002), these apparently contradictory findings may point to a greater overall emphasis on interdependence among Latino/a families, both in terms of expectations that the child contribute more to the household at an earlier age, yet assert his or her own agency (both behavioral and cognitive) at a later age.…”
Section: Core Cultural Values Among Latino/a Parentsmentioning
confidence: 92%
“…Although the importance of motivation=responsibility has been stressed by Latino immigrant parents of school-age and adolescent children (Azmitia, Cooper, Garcia, & Dunbar, 1996;Buriel, 1993;Okagaki & Sternberg, 1993;Torres, 2009), this study may be one of the first in which it is identified as a goal for children as young as preschool age. Furthermore, the final two short-term goal categories, salir adelante and sentirse cómodo, are more akin to U.S. EA socialization goals than typical Latino goals as reported in the literature .…”
Section: Ca Mothers' Goals For Their Preschool Childrenmentioning
confidence: 98%